2021
DOI: 10.1097/hjh.0000000000002742
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potassium on DNA methylation of aldosterone synthase gene

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…For a more in-depth understanding of these DEGs, we analyzed the selected genes for GO and REACTOME pathway enrichment analyses and found that GO terms and signaling pathways were significant. [106], FCN1 [107], CARNS1 [108], AMH (anti-Mullerian hormone) [109], E2F1 [110], PF4 [111], RPL3L [112], TRIM72 [113], HOXB4 [114], TP73 [115], KCNH2 [116], (advanced glycosylation end-product specific receptor) [117], SMPD3 [118], TYMP (thymidine phosphorylase) [119], RIPPLY3 [120], GREM1 [121], CYP11B2 [122], MYLK2 [123], WNT3A [124], MSX1 [125], COMP (cartilage oligomeric matrix protein) [126], FLI1 [127], ACTA1 [128], TCAP (titincap) [129], TUBB1 [130], TNNI3 [131], HSPB7 [132], DES (desmin) [133], RAP1B [134], TNNT1 [135], BHMT (betaine--homocysteine S-methyltransferase) [136], ANGPTL3 [137], CYP3A5 [138], KMO (kynurenine 3-monooxygenase) [139], HMGCS2 [140], AGXT2 [141], FABP1 [142], SLC22A12 [143], CUBN (cubilin) [144], MIOX (myo-inositol oxygenase) [145], FBP1 [146], ARG2 [147], FGF1 [148], CRY1 [149], PPARGC1A [150], UGT1A6 [151], ECHDC3 [152], CYP2C8 [153], ACOX2…”
Section: Discussionmentioning
confidence: 99%
“…For a more in-depth understanding of these DEGs, we analyzed the selected genes for GO and REACTOME pathway enrichment analyses and found that GO terms and signaling pathways were significant. [106], FCN1 [107], CARNS1 [108], AMH (anti-Mullerian hormone) [109], E2F1 [110], PF4 [111], RPL3L [112], TRIM72 [113], HOXB4 [114], TP73 [115], KCNH2 [116], (advanced glycosylation end-product specific receptor) [117], SMPD3 [118], TYMP (thymidine phosphorylase) [119], RIPPLY3 [120], GREM1 [121], CYP11B2 [122], MYLK2 [123], WNT3A [124], MSX1 [125], COMP (cartilage oligomeric matrix protein) [126], FLI1 [127], ACTA1 [128], TCAP (titincap) [129], TUBB1 [130], TNNI3 [131], HSPB7 [132], DES (desmin) [133], RAP1B [134], TNNT1 [135], BHMT (betaine--homocysteine S-methyltransferase) [136], ANGPTL3 [137], CYP3A5 [138], KMO (kynurenine 3-monooxygenase) [139], HMGCS2 [140], AGXT2 [141], FABP1 [142], SLC22A12 [143], CUBN (cubilin) [144], MIOX (myo-inositol oxygenase) [145], FBP1 [146], ARG2 [147], FGF1 [148], CRY1 [149], PPARGC1A [150], UGT1A6 [151], ECHDC3 [152], CYP2C8 [153], ACOX2…”
Section: Discussionmentioning
confidence: 99%
“…However, where and how do changes in DNA methylation take place in non-CpG promoter sites? We reported that stimulatory signals of potassium treatment led to DNA demethylation around transcription factor binding sites and a transcription start site, where the chromatin structure was relaxed [ 39 ] ( Figure 4 ). DNA demethylation was observed during two days of potassium treatment, while the highest level of demethylation was evident by seven days.…”
Section: Epigenetic Control Of Cyp11b2mentioning
confidence: 99%
“…DNA demethylation was observed during two days of potassium treatment, while the highest level of demethylation was evident by seven days. The CYP11B2 promoter demethylation increased gene expression [ 39 ] ( Figure 5 A).…”
Section: Epigenetic Control Of Cyp11b2mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 A shows the CpG sites of the CYP11B2 promoter region. Transcriptional activation by potassium gradually causes DNA demethylation around the CREB1- and NR4A-binding sites as well as a TSS over seven days, and its withdrawal reverses this process over the next seven days in H295R cells [ 62 ]. Although the CYP11B2 promoter is a non-CpG island promoter, each of the CREB1- and NR4A-binding sites (at positions −71/ −64 and positions −129/−114, respectively) contains one CpG dinucleotide, and these binding sites are crucial for the basal transcription activity.…”
Section: Contribution Of Dna Methylation To Human Cyp11b2 Transcriptionmentioning
confidence: 99%